MENGOPTIMALKAN FLUKS MAGNET PADA GENERATOR AC MENGGUNAKAN SUMBER EKSTERNAL UNTUK MENGHASILKAN TEGANGAN - Ahmat Susilo; Yudhi Yudhi; Surojo Surojo (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
A generator is a machine that is needed to produce energy that is almost used all over the world. There are two kinds of generator magnetic field generators, there are those that use permanent magnets and non-permanent magnets with generation using an excitation system. From the two magnetic sources above, I conducted research using non-permanent magnets aimed at knowing the magnetic flux produced. Because the magnetic flux produced is not constant, a study is needed to find out a good excitation source to produce a constant magnetic flux and produce electrical energy as desired. The generator has two main parts, namely the satator and the rotor where the stator is a stationary part and has the function of generating energy while the rotor is a moving part and has the function of generating a magnetic field. In my research, I changed the sator part as a generator of electrical energy. The results obtained from testing this non-permanent magnet generator are 6 experiments using different stator coils. From the results of these tests, the results of the AC power supply were obtained using a coil with the lowest inductance value (225uH) 0.049Vac and using a coil with the highest inductance value (49.8mH) 1.58Vac. From the test results, it can be concluded why the resulting voltage is too small for the magnetic flux generated because the value is not constant, it can affect the load, as well as rpm rotation and other things.